Forest Insecurity and the Dilemma of the Farmers-Herdsmen Crisis in Nigeria (Acta Universitatis Danubius. Relationes Internationales, 2023)
The objectives of the study are to examine the issues of the farmers-herdsmen crisis because of forest insecurity, identify the challenges that forest insecurity posed to farmers-herdsmen relationships, and interrogate the implications of these for food security in a country that seeks to diversify its economy from a dependence on oil to farming. The study finds that the main manifestations of forest insecurity in farmers-herdsmen relationships crises have included the crisis between farmers and herdsmen, herdsmen trespassing on farmland, insecurity of lives of forest users, poor initiation of government policies, breakdown of peace between farmers and herdsmen, and government’s loss of forest resources to n-state actors. The findings also reveal that the challenges forest insecurity posed to farmers and herdsmen have included massive loss of lives and property, loss of earning power, crippling socio-economic problems, and deepening of farmers/herdsmen crisis. The study recommends that government overhaul existing policies and provide adequate security for monitoring and control of Nigeria’s forests for safe and productive cultivation by all forest users.